How Far has Islamic Marketing Topics Been Researched? - Mimma Maripatul Uula; Nun Maziyyah (Islamic Marketing Review, 2022)
This study aims to look at the development of "Islamic Marketing" research around the world and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Islamic Marketing" which comes from the Scopus database with a total of 885 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Islamic Marketing" research development in the world. The results of the study found that in bibliometric author mapping the authors who published the most research on the theme of "Islamic Marketing" were El-Bassiouny N; Islami M.M; Alserhan B.A; Junaidi J; Kadirov D; Javari A; Marinov M; Henderson J.C; Sayuti K.M.; Amin H; El-Gohary H.; Eid R; Wilson J.A.J.; Hollensen S; Yassim M; Tieman M; Bran T; and Haq F.; Wong H.Y.. Furthermore, based on bibliometric keyword mapping, there are 3 clusters that can be a research path with topics related to (1)Islamic Marketing and Its Impact on the Business, Consumption and Tourism Industries, (2)Banking Industry and Islamic Marketing and (3)Islamic Marketing and Customer Loyalty. The most used words are market, customer, consumer, Islamic marketing, Islamic bank, service, religiosity, and Muslim consumer.